Study on Migration and Transformation of Sulfonamide Antibiotics in Livestock Manure-Soil-Plant-Water Systems - Weida YU; Jinrong QIU; Xiujuan WANG; Di XIA; Qianyi CAI; Jingwen ZENG; Jianli ZHOU (Guangdong nongye kexue, 2022)
【Objective】With the rapid development of large-scale livestock and poultry breeding industry, the pollution of sulfonamide antibiotics in livestock and poultry manure is becoming more and more prominent. The study aims to evaluate the migration and transformation characteristics of sulfonamide antibiotics in livestock manure in soil-plant-water system.【Method】The corn plants were planted in the soil without fertilizer, compound fertilizer, chicken manure and pig manure, and the concentrations of sulfonamide antibiotics in soil, leachate and plants at different growth periods of corn were determined by rotary evaporator and high performance liquid chromatograph(HPLC), then the adsorption or desorption characteristics and migration ability of sulfonamide antibiotics in livestock manure-soil system were studied.【Result】Most(67.65% and 42.74%)of sulfonamide antibiotics in the soil where chicken manure and pig manure were applied decomposed naturally, while the undecomposed sulfonamide antibiotics migrated to the deep soil layer(12.59% and 28.59%), and only a small amount (0.66% and 1.66%)of the antibiotics migrated to the soil leachate. The root was the main accumulation part of sulfonamide antibiotics, and no sulfonamide antibiotics were detected in corn fruit.【Conclusion】Sulfonamide antibiotics in livestock manure will accumulate in plants through soil, and root is the main accumulation part, therefore, root crops may be more susceptible to sulfonamide antibiotic pollution.